2006
DOI: 10.1007/s00259-006-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of FDG PET studies using standardised uptake values in multi-centre trials: effects of image reconstruction, resolution and ROI definition parameters

Abstract: Standardisation of acquisition, reconstruction and ROI methods is preferred for SUV quantification in multi-centre trials. Small unavoidable differences in methodology can be accommodated by performing a phantom study to assess inter-institute correction factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
215
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(222 citation statements)
references
References 15 publications
4
215
1
2
Order By: Relevance
“…SUV is dependent on parameters such as time after injection, ROI size, plasma glucose/insulin concentration, body weight, instrumental factors, partial volume effect, and the resolution of the PET unit [27]. Differences in any of these parameters might account for differences in the threshold SUV among studies.…”
Section: Discussionmentioning
confidence: 99%
“…SUV is dependent on parameters such as time after injection, ROI size, plasma glucose/insulin concentration, body weight, instrumental factors, partial volume effect, and the resolution of the PET unit [27]. Differences in any of these parameters might account for differences in the threshold SUV among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SUVs may not only change with different modes of acquisition (2D or 3D mode), but also with the use of different scanners, image reconstruction and data analysis software. A potential problem in the present use of combined PET-CT scanners is that SUVs may not necessarily show the same absolute values and the same degree of reliability as those obtained from stand-alone PET scanners, in which attenuation correction factors are calculated using external 511-keV rod sources (9). Variability in SUV methodology hampers direct comparison of results obtained in different studies and prevents comparison of results obtained in different centers (10).…”
mentioning
confidence: 99%
“…First, a calibration factor was calculated by dividing the actual SUV by the measured mean SUV in the phantom background to reduce interinstitutional SUV variability. 17 Second, a recovery coefficient (RC) was calculated as a function of sphere diameter to decrease the dependence of SUV on tumor size. 18 The mean SUV value was only used as a part of the phantom study, although maxSUV values were measured as a significant factor in each patient.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] However, many factors (such as patient preparation procedures, scan acquisition, image reconstruction, and data analysis) affect SUV. 20,21 Westerterp et al 17 reported that an up to 30% variation in SUV quantification among 3 institutions can pose a serious problem when performing multicenter studies. This explains why very few multicenter studies to date have attempted to target SUV on PET.…”
mentioning
confidence: 99%